The Effects of Crude Oil and Dispersed Crude Oil On Tropical Ecosystems: Long-Term Seagrass, Mangrove, and Coral Studies - Baca, Bart J.; Snedaker, Samuel C.; Dodge, Richard E., (editor); Knap, Anthony H.; Sleeter, Thomas D. (NSUWorks, 1996)
Tropical ecosystems typically contain three sensitive and important habitats: seagrass beds, mangrove forests, and coral reefs. The effects of oil on these systems have been studied individually in the laboratory with few long-term studies on the ecosystem as a whole. Described in this report is an experiment carried out on the Caribbean coast of Panama (Bocas del Toro). Prudhoe Bay crude oil and dispersed crude oil were released on separate sites, each containing seagrass (Thalassia testudinum), mangrove (Rhizophora mangle), and coral habitats representative of ecosystems in Caribbean waters. The short-term (two-year) results of the study are presented along with those from the long-term (+10 year) re-assessment. The study was a simulation of the “worst case” exposure level for dispersed oiland a high exposure level for crude oil. The application of oil and dispersed oil was monitored regularly over a 23 hour period, the sites being monitored periodically over two years, and re-examined 10 years after the experiment. Assessments were made over time of the distribution and extent of contamination by hydrocarbons and the short- and long-term effects on survival, abundance, and growth of the dominant flora and fauna in each habitat. In the short term, chemically dispersed oil caused declines in the abundance of invertebrates, including corals, but the effects had essentially disappeared over the long term. Fresh, untreated oil had severe, long-term effects on survival of mangroves and associated fauna, but relatively minor effects on seagrasses, corals, and associated organisms. The results of this study provide definitive data through which decisions may be made about the use and non-use of chemical dispersants, while adding to the knowledge of hydrocarbon effects and fate in the ecosystems. The methods and results of this controlled field experiment also have implications for the effective design of microcosm and mesocosm toxicity studies.